Growing Up Urban: Hyena Foraging Groups and Social Structure at a City Waste Dump - Struller, Franziska; Bauer, Hans; Yirga, Gidey; Vos, Matthijs (Frontiers in Conservation Science, 2022)
Urban spotted hyenas (Crocuta crocuta) in Ethiopia are a prime example of large carnivores coexisting peacefully with people in a human-dominated landscape, providing a valuable waste-removal service. To gain insight in how this urban lifestyle is transmitted across generations, we studied hyena group composition at the city waste dump of Mekelle, a regional capital in northern Ethiopia. We found that hyena cubs and sub-adults foraged with adults in groups of highly variable composition. Young urban hyenas already take part in a fission-fusion dynamic that is also characteristic of hyenas in the wild. They do not seem to learn from, or in stable proximity to, only one or few close reference adults. Social network analysis revealed no clusters among these dump-visiting hyenas, that furthermore outnumber any hyena clan in non-urban areas. All individuals were more or less equally connected to each other, and each hyena had a few connections, but to different individuals. All cubs and sub-adults were connected to each other, over a maximum of four links. Hardly any aggression was observed at the waste dump. Hyenas rather peacefully shared the abundance of food. A much larger number of urban hyenas shares this waste dump at night than would fit into a single daytime resting site. Hyenas appear to commute from different dens and resting sites located around the city, but we have no information on their behaviour and group composition away from the dump. We observed no defence of any part of the dump area by any of the foraging groups. In absence of territorial behaviour at this city site, the clan concept does not seem to apply to these urban hyenas. At the waste dump all individuals behaved as peacefully sharing members of conflict-free foraging groups. Perhaps this is what most strikingly defines their urbanity.